A nootropic effect of Moringa oleifera on Ach and ChAT activity in colchicine induced experimental rat model of Alzheimer's disease: Possible involvement of antioxidants - Chandan Roy (Al Ameen Medical College, 2014)
Context: The fruit and leaf of Moringa oleifera (MO) is an important ingredient of 'Kusmanda lehyam' (Ayurvedic medicine), which is widely used, in nervous disorders. Objective: To determine the cognition facilitating effect of MO leaf extract in colchicine induced experimental rat model of AD and to investigate the role of central cholinergic system in the nootropic effect of MO leaf extract with the possible involvement of antioxidant enzymes. Materials and methods: The behavior study, Acetylcholine concentration, cholineacetyl transferase activity, antioxidant level such as, superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH) and lipid peroxidation (LPO) level were studied in different parts of the brain such as frontal cortex (FC) and hippocampus (HPC) in colchicine induced experimental Alzheimer rat model before and after treatment with MO. Results: MO (250 mg/kg p.o.) induced statistically significant reversal of colchicine induced cognitive deficits. MO (250 mg/kg p.o.) markedly induced frontal, cortical and hippocampal concentrations of Ach and ChAt activity, the effects being statistically significant on days 7, 14 and 21 respectively. Moreover, MO significantly increased SOD, CAT, GSH activities and significantly decreased LPO level on day 7, 14 and 21 respectively. Discussion and conclusion: The aqueous pulp extract of MO (250 mg/kg body weight) containing vit- A, C, E results significant protection in the level of antioxidant status in frontal cortex and hippocampus after a certain period of co administration on colchicine induced oxidative stress without causing any general and metabolic toxicity and possibly thereby induced frontal cortical and hippocampal concentration of Ach and ChAT activity.